2021
DOI: 10.1111/jcpt.13413
|View full text |Cite
|
Sign up to set email alerts
|

Association between potentially inappropriate medication and adverse drug reactions in hospitalized elderly patients

Abstract: What is known and objective The Beers, European Union (EU) and Screening Tool of Older Persons’ potentially inappropriate Prescription (STOPP) criteria were developed to improve the safe use of medicines in the elderly. However, the predictive validity of existing criteria to detect adverse drug reactions (ADRs) remains unexplored. The objective of the current study was to determine whether the 2019 Beers, 2015 STOPP or 2015 EU potentially inappropriate medicine (PIM) criteria were associated with ADRs. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…In this study, it was shown that there is a relationship between PIP using explicit prescription tools, Beers criteria and STOPP/START criteria, and the development of in-hospital complications related to ADR. A high prevalence of PIP was found, like that reported in the literature in hospitalized older adult patients 16,17 . With respect to ADR, a higher prevalence was found than that reported in the literature in community dwelling, a study carried out in a hospital reported a similar prevalence 18 .…”
Section: Discussionsupporting
confidence: 83%
“…In this study, it was shown that there is a relationship between PIP using explicit prescription tools, Beers criteria and STOPP/START criteria, and the development of in-hospital complications related to ADR. A high prevalence of PIP was found, like that reported in the literature in hospitalized older adult patients 16,17 . With respect to ADR, a higher prevalence was found than that reported in the literature in community dwelling, a study carried out in a hospital reported a similar prevalence 18 .…”
Section: Discussionsupporting
confidence: 83%
“…In our retrospective patient records review, we found that almost none contained a medication review, although it would be clearly beneficial for a majority of these multimorbid and polypharmacy patients 7 8 25 52. To illustrate, doctors’ medication review may reduce PIMs,53 which, if not stopped, may lead to ADRs,54 55 hospitalisation,56 57 increased mortality,58 and new falls and fractures 8. A majority of doctors considered PIMs when they performed a medication review, but needed more time to be able to complete medication reviews for more of their patients.…”
Section: Discussionmentioning
confidence: 95%
“…99 Common tools for identifying PIMs include the Medication Appropriateness Index (MAI), HEDIS DAE, Beer's criteria, STOPP/ START criteria and EU-7-PIM list [Figure 3(c)]. [106][107][108][109] Wang et al 110 used Beer's criteria, STOPP/START criteria, and the EU-7-PIM list to evaluate the use of drugs in 560 elderly inpatients and found that Beer's criteria best predicted avoidable ADRs. However, for the elderly in Africa (Nigeria and South Africa), PIMs identified using Beer's criteria did not correlate to ADRs in hospitalized patients.…”
Section: Use Of Medication In Elderly Patientsmentioning
confidence: 99%